OPTIMALISASI PENERAPAN DIGITAL MARKETING DI UMKM DEPNAMOR BANDUNG - SUSILAWATI, ERNA (ABISATYA DINAMIKA ISWARA PUBLISHING, 2023)
The existence of the internet which makes information spread quickly without any distance and time limitations that can be accessed anywhere and anytime makes a lot of changes. The emergence of the Covid 19 pandemic has also had such a big impact on life in the world, where because of this pandemic it has significantly increased the use of internet usage. How could it not be, due to social restrictions and social distancing in order to inhibit the spread of the Covid 19 virus, various things are done online. Of course this also applies to trade. On the other hand, this pandemic has actually boosted the use of market places and social media, mainly used as promotional tools or also as a place to sell online. However, many people/companies/business units/MSMEs have used market places or social media platforms as a place to sell but not optimally. They are only limited to using it without being accompanied by a strategy to maximize sales on these platforms. This is also experienced by the UMKM Ministry of National Defense which produces bow ties and long ties. For increasing their sales figures, it is necessary to implement a digital marketing strategy that is in accordance with the conditions of the company.